Meta-analysis of randomized controlled trials and individual patient data comparing minimally invasive with open oesophagectomy for cancer - Müller, Beat P.; Probst, Pascal; Nienhüser, Henrik; Fazeli, Shila Marlen; Senft, Jonas; Kalkum, Eva; Heger, Patrick; Warschkow, R.; Nickel, Felix; Billeter, Adrian; Grimminger, P. P.; Gutschow, C.; et al. (The British journal of surgery, 2021)
Minimally invasive oesophagectomy (MIO) for oesophageal cancer may reduce surgical complications compared with open oesophagectomy. MIO is, however, technically challenging and may impair optimal oncological resection. The aim of the present study was to assess if MIO for cancer is beneficial.A systematic literature search in MEDLINE, Web of Science and CENTRAL was performed and randomized controlled trials (RCTs) comparing MIO with open oesophagectomy were included in a meta-analysis. Survival was analysed using individual patient data. Random-effects model was used for pooled estimates of perioperative effects.Among 3219 articles, six RCTs were identified including 822 patients. Three-year overall survival (56 (95 per cent c.i. 49 to 62) per cent for MIO versus 52 (95 per cent c.i. 44 to 60) per cent for open; P = 0.54) and disease-free survival (54 (95 per cent c.i. 47 to 61) per cent versus 50 (95 per cent c.i. 42 to 58) per cent; P = 0.38) were comparable. Overall complication rate was lower for MIO (odds ratio 0.33 (95 per cent c.i. 0.20 to 0.53); P < 0.010) mainly due to fewer pulmonary complications (OR 0.44 (95 per cent c.i. 0.27 to 0.72); P < 0.010), including pneumonia (OR 0.41 (95 per cent c.i. 0.22 to 0.77); P < 0.010).MIO for cancer is associated with a lower risk of postoperative complications compared with open resection. Overall and disease-free survival are comparable for the two techniques.Oesophagectomy for cancer is associated with a high risk of complications. A minimally invasive approach might be less traumatic, leading to fewer complications and may also improve oncological outcome. A meta-analysis of randomized controlled trials comparing minimally invasive to open oesophagectomy was performed. The analysis showed that the minimally invasive approach led to fewer postoperative complications, in particular, fewer pulmonary complications. Survival after surgery was comparable for the two techniques.
Gesehen am 28.01.2022